540 Age Trends in Sleep Across the Lifespan: Findings from the Pittsburgh Lifespan Sleep Databank. (3rd May 2021) - Wallace, Meredith; Kissel, Nicholas; Hall, Martica; Germain, Anne; Matthews, Karen; Troxel, Wendy; Franzen, Peter; Buysse, Daniel; Roecklein, Kathryn; Gunn, Heather; Hasler, Brant; Goldstein, Tina; et al.
Abstract: Introduction: Sleep continuously changes over the human lifespan and it does so across multiple dimensions, including duration, timing, efficiency, and variability. Although studies focused on specific developmental periods have shown age-related changes in sleep, methodological differences make it difficult to synthesize information across studies to fully understand precisely when these sleep changes occur. Our goal was to use individual-level actigraphy and self-report sleep data from a single site to characterize age trends and sex differences in actigraphy and self-report sleep dimensions across the healthy human lifespan. To accomplish this goal, we developed the Pittsburgh Lifespan Sleep Databank (PLSD), a large aggregate databank of participants from sleep research studies conducted at the University of Pittsburgh. Methods: In the present analysis, we included N=1, 070 PLSD participants from 21 studies without a major psychiatric, sleep, or medical condition. We used Generalized Additive Models to examine flexible, potentially non-linear relationships between age and sleep dimensions (actigraphy and self-report duration, efficiency, and timing; actigraphy variability) from ages 10 to 87. We also examined whether these sleep characteristics differed by sex across the lifespan. Results: The most dramatic age-related trends were observed in sleep timing. Actigraphy and self-report sleep onset time shifted later between ages 10–18 and then shifted earlier again during the 20s. Actigraphy and self-report wake-up time also shifted earlier during the mid-20s through late 30s. Self-report duration became shorter from approximately ages 10–20. Self-report sleep efficiency and actigraphy variability both decreased over the entire lifespan. Relative to males, females tended to have earlier self-report sleep onset, higher actigraphy sleep efficiency, and longer actigraphy duration. Conclusion: By focusing on lifespan sleep rather than specific age segments of the samples, we can provide a unified assessment of age-related changes and sex differences from childhood through older adulthood. An understanding of age trends and sex differences in sleep in healthy individuals – and explicating the timing and nature of these difference – can be used to identify periods of sleep-related risk or resilience and guide intervention efforts. Support (if any): University of Pittsburgh Clinical and Translational Science Institute (UL1TR001857).